2013
DOI: 10.2139/ssrn.2206201
|View full text |Cite
|
Sign up to set email alerts
|

Impact of External Knowledge Acquisition Strategies on Innovation – A Comparative Study Based on Dutch and Swiss Panel Data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Forés and Camisón (2016) found that a firm's innovation performance relies on external and internal knowledge sources to reduce environmental impact and improve energy efficiency. While, Arvanitis, Lokshin, Mohnen, and Wörter (2015) have identified that customer knowledge is important for the firms pursuing innovation. Many scholars have reported that external knowledge resources positively contribute to supplier innovation performance improvements (Xie, Zou, & Qi, 2018).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Forés and Camisón (2016) found that a firm's innovation performance relies on external and internal knowledge sources to reduce environmental impact and improve energy efficiency. While, Arvanitis, Lokshin, Mohnen, and Wörter (2015) have identified that customer knowledge is important for the firms pursuing innovation. Many scholars have reported that external knowledge resources positively contribute to supplier innovation performance improvements (Xie, Zou, & Qi, 2018).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…For instance, Polder et al (2010) find that ICT investment is an important driver of organizational innovation, which itself complements product and process innovations in achieving higher TFP growth. Arvanitis et al (2015) find complementarities between external knowledge acquisition strategies such as "buy" and "cooperate" and the firm's own innovation activities. Aw et al (2008) find a positive interaction effect between R&D and export activities in terms of firms' productivity; participating in export markets raises the returns on R&D. However, empirical contributions on the complementarity of R&D and fixed capital investments is scarce.…”
Section: Innovation Performance: Complementarity Between Randd and Fixementioning
confidence: 99%
“…After solving the question about the direction of causality between R&D and investment, we can order the effects and investigate their complementarity in terms of the commercial success of innovative products, whereby we argue that R&D increases the return on fixed capital investments. Although the literature provides comprehensive empirical studies addressing various types of complementarities (e.g., Milgrom and Roberts 1995;Arvanitis et al 2015;Polder et al 2010), the complementary relationship in terms of the commercial success of innovative products between R&D and fixed capital has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%